APIs, standards, and enabling infrastructure. - Cerf, Vinton G. (Communications of the ACM, 2019)
The article discusses application programming interfaces (API) and their use in subroutine protocols. It states that protocols above the Internet Protocol layer can utilize a number of alternative network technologies underlying it without knowing how those layers function and comment how API possess similar properties. It talks about the scrutiny of common libraries for security and reliability which a common set of APIs reference.